أثر قلق المنافسة على الأداء المهاري والمردود البدني لدى لاعبي كرة القدم أكابر. - مهدي يوسف/براهيمي زكرياء (Institut d’Éducation Physique et Sportive / UNIVERSITY OF MOSTAGANEM, 2025)
هدفت هذه الدراسة إلى الكشف عن أثر قلق المنافسة على الأداء المهاري والمردود البدني لدى لاعبي كرة القدم أكابر. اعتمد الباحث على المنهج الوصفي بأسلوب المسح، مستعينًا بأداة الاستبيان الذي تضمن محورين رئيسيين بواقع (12) سؤالًا لكل محور بصيغة نعم/لا/أحيانًا. تم تطبيق الأداة على عينة قصدية مكونة من (38) لاعبًا ينشطون ضمن صفوف نادي الأمل الرياضي عمي موسى بولاية غيليزان. توصلت النتائج إلى أن ارتفاع مستوى القلق يؤثر سلبًا على الأداء المهاري ويضعف المردود البدني أثناء المنافسة. أوصت الدراسة بضرورة إدماج التحضير النفسي ضمن برامج التدريب اليومية وضرورة اهتمام المدربين والأخصائيين النفسيين بإعداد اللاعبين ذهنيًا لمواجهة ضغوط المنافسة. // // // // // // // The Impact of Competitive Anxiety on Technical Performance and Physical Output in Senior Football Players. This study aimed to investigate the impact of competitive anxiety on both technical performance and physical output among senior football players. The researcher adopted the descriptive survey method and designed a questionnaire consisting of two main axes with 12 closed-ended items each (Yes / No / Sometimes). The instrument was administered to a purposive sample of 38 players from AmalSportifAmmiMoussa Club, ghilizane. The findings revealed that high levels of competitive anxiety negatively affect players' technical performance and reduce their physical efficiency during matches. The study recommended integrating psychological preparation into daily training programs and emphasized the importance of coaches and sports psychologists supporting players mentally to cope with competition stress.
LES-2025-14
Keywords: قلق المنافسات; الأداء المهاري; المردود البدني; لاعبي كرة القدم اكابر